Glutathione Transferase Classes Alpha, Pi, and Mu: GSH Activation Mechanism - Daniel F A R Dourado (2010)
Since the early 1960s, glutathione transferases (GSTs) have been described as detoxification enzymes. In fact, GSTs are the most important enzymes involved in the metabolism of electrophilic xenobiotic/endobiotic compounds. These enzymes are able to catalyze the nucleophilic addition of glutathione (GSH) sulfur thiolate to a wide range of electrophilic substrates, building up a less toxic and more soluble compound. Cytosolic classes alpha, pi, and mu are the most extensively studied GSTs. However, many of the catalytic events are still poorly understood. In the present work, we have resorted to density functional theory (DFT) and to potential of mean force (PM F) calculations to determine the GSH activation mechanism of GsTP1-I and GSTMI-1 isoenzymes. For the GSTPI-1 enzyme, we have demonstrated that a water molecule, after an initial conformational rearrangement of GSH, can assist a proton transfer between the GSH cysteine thiol (GSH-SH) and the GSH glutamate alpha carboxylate (GSH-COO(-)) groups. The energy barrier associated with the proton transfer is 11.36 kcal.mol(-1). The GSTMI-1 enzyme shows a completely different behavior from the previous isoenzyme. In this case, two water molecules, positioned between the GSH-SH and the N atom of His 107, working like a bridge, are able to promote the proton transfer between these two active groups with an energy barrier of 7.98 kcal. mol(-1). All our results are consistent with all the enzymes kinetics and mutagenesis experimental studies.